2009
DOI: 10.1107/s1600536809030256
|View full text |Cite
|
Sign up to set email alerts
|

4-(Benzylideneamino)benzenesulfonamide

Abstract: The title compound, C13H12N2O2S, formed by Schiff base condensation of benzaldehyde with sulfanilamide, crystallizes as discrete mol­ecular species linked by N—H⋯N and N—H⋯O hydrogen bonds between the sulfamide nitro­gen H atoms and the aza­methine N and one sulfamide O atom, respectively, forming a two-dimensional array in the bc plane. The aza­methine group is rotated slightly out of the benzaldehyde benzene plane [C—C—C—N torsion angle = 8.1 (3)°], while the dihedral angle between the two benzene rings is 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…For benzene sulfonamide derivates, Loughrey et al [46] reported the bond lengths S 24 [47] are in agreement with the corresponding values of the title compound.…”
Section: Geometrical Parameters and First Hyperpolarizabilitysupporting
confidence: 62%
“…For benzene sulfonamide derivates, Loughrey et al [46] reported the bond lengths S 24 [47] are in agreement with the corresponding values of the title compound.…”
Section: Geometrical Parameters and First Hyperpolarizabilitysupporting
confidence: 62%
“…[25] These lengths have been reported 1.6023, 1.6059, 1.7974 and 1.8635 Å by Chandran et al [26], respectively. In our study, S1-O1, O2, N1, C4 have been computed 1.456, 1.458, 1.720 and 1.794 Å at the B3LYP/6-311G++(d,p) level.…”
Section: Geometric Structurementioning
confidence: 81%
“…1) with bond lengths in the normal range expected for this class of compound [46][47][48][49][50]. The molecular structure of the compound is not planar with a dihedral angle C11AC12AS1AN2 of 72.1°and C13AC12AS1AN2 of À104.5°between the plane of the benzene ring and the ASANH 2 .…”
Section: Crystal Structurementioning
confidence: 96%